Risk factors for late presentation among glaucoma patients attending three referral hospitals in South-East Nigeria: case–control study - Onyinye Onyia; Eberechukwu Achigbu; Ifeoma Ejiakor; Nkechi Uche; Ubochi Chinemerem; Chimdia Ogbonnaya; Chimdi M Chuka-Okosa; Catey Bunce; Covadonga Bascaran (Cogent Public Health, 2022)
Late presentation in glaucoma has been associated with rapid deterioration of visual fields and blindness even with good and effective treatment options. Glaucoma prevalence and risk of blindness is higher among the Igbo tribe, who dominate the Eastern part of Nigeria, hence the focus of this study in this area to determine modifiable risks for late presentation in glaucoma. This was an observational, hospital-based, comparative study at three tertiary hospitals. All eligible, consenting participants were examined and researcher-recorded questionnaire administered. Data was entered, validated and imported into Stata version 15.0; appropriate descriptive measures of central tendencies were presented with tables and maps. Univariate, multiple logistic regression and pairwise correlation analysis identified statistically significant risks at p-value of <0.05. 303 participants were enrolled with a mean (SD) age of 56.58 (15.63) years. The adjusted odds of presenting late were found to be 57% lower among females (CI 0.27 to 0.69), 1.73 times higher with each year increase (CI 1.42 to 2.11) and 2.31 times among hypertensives (CI 1.39 to 3.85). There were reduced adjusted odds ratio; 0.55 for participants living in urban areas compared to rural (p 0.02) and 0.52 for those who have heard about glaucoma prior to diagnosis (p 0.01). Increasing age, male sex, rural and non-awareness of glaucoma are identified risk for late presentation. Community-based health promotion activities can be explored to bridge this gap through targeted and cost-effective approaches involving existing health-care delivery systems.